MANAJEMEN PENGEMBANGAN SDM GURU BERBASIS ETIKA ISLAM DALAM PENGELOLAAN KONFLIK KERJA UNTUK MENINGKATKAN PROFESIONALISME GURU MADRASAH UNGGUL: KAJIAN LITERATUR - Hidayati, Zulfa Rahmat; Latif, Mukhtar; Taridi, Muhamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to conceptually examine the integration of teacher human resource development (HRD) management based on Islamic ethics in managing workplace conflict to enhance teacher professionalism, particularly in excellent madrasahs. This study employs a literature review approach by analyzing theories, concepts, and previous empirical studies related to teacher human resource development, Islamic ethics, workplace conflict management, and teacher professionalism within the context of madrasah education. The findings indicate that teacher professionalism is not solely determined by pedagogical and professional competencies, but also by the internalization of Islamic ethical values that shape work attitudes, moral integrity, and the ability to manage workplace conflicts constructively. Islamic ethics function as both a normative and strategic foundation underpinning teacher human resource development and conflict management practices in madrasah institutions. This review also identifies a research gap, particularly the limited number of studies that comprehensively integrate teacher human resource development, Islamic ethics, and workplace conflict management within a single conceptual framework, especially in the context of excellent madrasahs that face high performance standards and complex organizational dynamics. Therefore, this article proposes a conceptual framework as a theoretical foundation for future empirical research and the development of Islamic educational management practices.